The Relationship Between The Total Count of Leukocyte Types and Formahldehyde Induction in Wistar Rats - Anak Agung Bagus Tito Indra Prawira Negara; Anak Agung Ayu Niti Wedayani; Bayu Tirta Dirja (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Formaldehyde is a chemical compound with a high level of toxicity. In the industrial sector, formaldehyde is commonly found in cosmetic products, resins, adhesives, plastics, and wood products. Therefore, the objective of this research is to determine the effect of formaldehyde induction with concentrations of 20 ppm, 30 ppm, and 40 ppm on the total count of leukocyte types. This study is a qualitative research with a true experimental design employing a post-test only control group design. The study used male Wistar rats (Rattus norvegicus) totaling 24 individuals, which were divided into 4 groups: a control group and 3 treatment groups. Each group consisted of 6 rats induced with formaldehyde at concentrations of 20 ppm, 30 ppm, and 40 ppm. The Wistar rats will be terminated, and retro-orbital blood sampling will be conducted to count the various types of leukocytes in order to determine whether there are differences in leukocyte type counts among rats induced with formaldehyde. Data analysis will employ the Kruskal-Wallis test. The results of this study showed that there was a statistically significant difference (p <0.05) between formaldehyde and the total count of leukocyte types. In this study, it was found that there is a decrease in the total count of leukocyte types in the formaldehyde-exposed groups at 40 ppm, 30 ppm, and 20 ppm when compared to the control group.